Unmasking Digital Deviance: Analyzing Cybercrime Trends via Social Media in Pakistan: https://doi.org/10.55966/assaj.2025.4.1.064 - Fatima Rida Suddle (Corresponding Author); Samreen Pervaiz; Sehar Nawaz (`, 2025)
The proliferation of social media in Pakistan has led to a significant rise in cybercrime, posing serious challenges to individuals, society, and legal systems. This paper examines the historical context and evolution of cybercrime, its conceptual foundations, and its manifestation on social media platforms in Pakistan. By analyzing the notion of crime through the perspectives of eminent jurists such as John Austin, Jeremy Bentham, and J.W. Cecil Turner, the study establishes the essential elements of criminal conduct and their applicability to the digital domain. The paper traces the origins of cybercrime from early telegraph manipulations in the 19th century to the sophisticated mobile-based threats of the contemporary era, highlighting the adaptive nature of cybercriminals and the vulnerabilities of emerging technologies. Focusing on the Pakistani context, the research identifies six major categories of social media-related cybercrimes: phishing and social engineering, hacking, malware dissemination, identity theft, spamming, and cyberbullying/harassment. The paper underscores the pressing need for comprehensive legal frameworks, enhanced digital literacy, and robust cybersecurity measures to combat the escalating threat of cybercrime. It advocates for a multi-stakeholder approach, encompassing legislative reform, institutional enforcement, public awareness, and private sector cooperation, to mitigate the harmful consequences of digital offenses and protect individuals’ rights in cyberspace. The research contributes to the understanding of cybercrime’s conceptual underpinnings, historical development, and contemporary manifestations, while emphasizing the urgency of effective countermeasures in Pakistan’s rapidly evolving digital landscape. Keywords: Social Media, Internet, Cybercrime, Digital Deviance, Pakistan